Heterostructural composite of few‐layered MoS2/hexagonal MoO2 particles/graphene as anode material for highly reversible lithium/sodium storage. (29th October 2019) - Wu, Manman; Liu, Cong; Ma, Tengfei; Tang, Mingyi; Shen, Jiandong; Ji, Hongmei; Yang, Gang
Summary: The heterostructural construction of metal disulfide/oxide is essential in the electrochemical performance as anode material for lithium‐ and sodium‐ion batteries (LIBs and SIBs). In this work, an integrated composite of molybdenum disulfide (MoS2 ) and hexagonal molybdenum dioxide (MoO2 ) together enwrapped in reduced graphene oxide (rGO) is synthesized under hydrothermal condition. In the pelletizing MoS2 ‐MoO2 /rGO composite, rGO as substrate effectively prevents the restacking and pulverization of MoS2 ‐MoO2 during a long cycling process. Meanwhile, the synergistic effect among the MoS2, MoO2, and rGO components are responsible for abundant active sites and shorten ionic transport channels. When evaluating as anode material for LIB, MoS2 ‐MoO2 /rGO sample presents excellent cyclic performance and still delivers a high capacity of 1062.3 mA h g −1 after 120 cycles at 0.2 A g −1 ; evaluating in a SIB at 0.04 A g −1, it presents excellent cyclic performance and delivers 430 mA h g −1 at the 80th cycle. The heterostructural composite MoS2 ‐MoO2 /rGO is one of the candidate anode materials for high‐performance LIB and SIB. Abstract : An integrated composite of few layer MoS2 and hexagonal MoO2 nanoplates together enwrapped in reduced graphene oxide (rGO) is successfully synthesized. rGO effectively prevents the restacking and pulverization of MoS2 ‐MoO2 during long cycling, and heterostructural MoS2 ‐MoO2 /rGO supply abundant active sites. MoS2 ‐MoO2 /rGO sample exhibits capacity of 1062.3 mA h g −1 after 120 cycles at 0.2 A g −1 (for LIB), and it also delivers a good reversible capacity of 430 mA h g −1 at 0.04 A g −1 after 80 cycles (for SIB).